Good practice in occupational health services - Certification of stroke as an accident at work. Need for secondary prevention in people returning to work after acute cerebrovascular events - Andrzej Marcinkiewicz; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2015)
The classification of an acute vascular episode, both heart infarct and stroke, as an accident at work poses difficulties not only for post accidental teams, but also to occupational health professionals, experts and judges at labor and social insurance courts. This article presents the case of a 41-year-old office worker, whose job involved client services. While attending a very aggressive customer she developed solid stress that resulted in symptoms of the central nervous system (headache, speech disturbances). During her hospitalisation at the neurological unit ischemic stroke with transient mixed type aphasia was diagnosed. Magnetic resonance imaging (MRI) scan of the head revealed subacute ischemia. After an analysis of the accident circumstances, the employer's post accidental team decided that ischemic stroke had been an accident at work, because it was a sudden incident due to an external cause inducing work-related traumatic stroke. As a primary cause tough stress and emotional strain due to the situation developed while attending the customer were acknowledged. During control medical check up after 5 months the patient was found to be fit for work, so she could return to work. However, it should be noted that such a check up examination of subjects returning to work after stroke must be holistic, including the evaluation of job predispositions and health education aimed at secondary prevention of heart and vascular diseases with special reference to their risk factors. Med Pr 2015;66(4):595-599